Neurogenic mechanisms for locomotor-respiratory coordination in mammals - Juvin, Laurent; Colnot, Eloïse; Barrière, Grégory; Thoby-Brisson, Muriel; Morin, Didier (Frontiers in Neuroanatomy, 2022)
Central motor rhythm-generating networks controlling different functions are generally considered to operate mostly independently from one another, each controlling the specific behavioral task to which it is assigned. However, under certain physiological circumstances, central pattern generators (CPGs) can exhibit strong uni- or bidirectional interactions that render them closely inter-dependent. One of the best illustrations of such an inter-CPG interaction is the functional relationship that may occur between rhythmic locomotor and respiratory functions. It is well known that in vertebrates, lung ventilatory rates accelerate at the onset of physical exercise in order to satisfy the accompanying rapid increase in metabolism. Part of this acceleration is sustained by a coupling between locomotion and ventilation, which most often results in a periodic drive of the respiratory cycle by the locomotor rhythm. In terrestrial vertebrates, the likely physiological significance of this coordination is that it serves to reduce the mechanical interference between the two motor systems, thereby producing an energetic benefit and ultimately, enabling sustained aerobic activity. Several decades of studies have shown that locomotor-respiratory coupling is present in most species, independent of the mode of locomotion employed. The present article aims to review and discuss mechanisms engaged in shaping locomotor-respiratory coupling (LRC), with an emphasis on the role of sensory feedback inputs, the direct influences between CPG networks themselves, and finally on spinal cellular candidates that are potentially involved in the coupling of these two vital motor functions.